(untitled) (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The rapid advancement of information and communication technology has transformed interactions with financial institutions, particularly through digital or branchless banking. Bank Central Asia (BCA), a leading private bank, has introduced Blu BCA Digital, a digital banking application designed to meet the growing demand for convenient banking solutions. Despite its promising features, Blu BCA Digital faces significant challenges due to the increasing number of competing digital banking platforms. This study aims to assess users’ intentions to adopt Blu BCA Digital using the Technology Acceptance Model (TAM). A quantitative approach was employed, utilizing questionnaires distributed to 159 Blu BCA customers in DKI Jakarta, with data analyzed using SmartPLS 3.2.9 software and the Partial Least Squares (PLS) method. The results indicate that perceived ease of use and perceived usefulness positively and significantly affect users’ attitudes toward the application and their behavioral intentions to use it. Furthermore, attitude toward use significantly influences behavioral intention, and it partially mediates the relationship between perceived ease of use, perceived usefulness, and behavioral intention to use. Based on these findings, several strategic implications for digital banks are proposed. Enhancing user experience by addressing technical issues and optimizing interface design, demonstrating clear benefits to increase perceived usefulness, and proactively managing security concerns are critical. Additionally, providing digital literacy training can overcome barriers to adoption. These strategies are essential for improving user satisfaction and adoption rates. The study concludes that understanding user perceptions through TAM is crucial for developing effective digital banking strategies and suggests that future research should explore additional factors influencing digital banking adoption and consider longitudinal studies to track changes in user behaviors over time.